Lot splitting under load-limiting order release in high-variety shops: an assessment by simulation - Thürer, M. (2019)
Lot splitting is an important approach for shops that compete on short delivery times. Similarly, such shops can benefit from load-limiting order release mechanisms that balance workloads and regulate throughput times. Yet few studies have examined the combined effect of lot splitting and load-limiting order release. We use simulation to assess the combined effect of lot splitting and Paired-cell Overlapping Loops of Cards with Authorization (POLCA), an important load-limiting order release mechanism in the context of time-based competition. The experimental design includes different lot sizes, lot transfer policies, and POLCA quanta, i.e. the limit on the size of jobs represented by a single POLCA card. Lot splitting improves performance if lots can proceed independently as this ensures the quick replenishment of queues at downstream stations. However, we find that enforcing the synchronization of all lots that make up a job at every routing step leads to a deterioration in performance. This extends previous research, which appears to have overemphasized the positive effects of lot splitting. Meanwhile, although POLCA cards were originally used to represent lots, we demonstrate that using cards to represent a certain amount of workload can improve percentage tardy performance. This may also have resonance with other card-based solutions, including kanban.